2015
DOI: 10.1074/jbc.m115.642538
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization Mediated by a Divergent Forkhead-associated Domain Is Essential for the DNA Damage and Spindle Functions of Fission Yeast Mdb1

Abstract: Background: Fission yeast Mdb1 is homologous to mammalian MDC1, but the extent of conservation is unclear. Results: A previously unrecognized FHA domain in Mdb1 mediates a functionally important homodimerization. Conclusion: FHA domain-mediated dimerization is a conserved feature of MDC1 family proteins. Significance: This study extends our understanding of the function, mechanism, and evolution of MDC1 family proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This internal deletion disrupted the self-interaction of Atg11 To determine whether mediating homodimerization is the only function of the C terminal part of Atg11(522-583), we tested whether this part can be replaced by a heterologous dimerization domain. We fused a 32-amino-acid-long homodimerizing leucine zipper motif (LZ) (Luo et al, 2015) to Atg11 fragments, and examined the ability of the fusion proteins to complement the autophagy phenotype of atg11Δ. LZ fusion fully restored the ability of Atg11(522-552) to complement atg11Δ ( Figures 3F and 3G).…”
Section: Atg11(546-583) Mediates Homodimerizationmentioning
confidence: 99%
“…This internal deletion disrupted the self-interaction of Atg11 To determine whether mediating homodimerization is the only function of the C terminal part of Atg11(522-583), we tested whether this part can be replaced by a heterologous dimerization domain. We fused a 32-amino-acid-long homodimerizing leucine zipper motif (LZ) (Luo et al, 2015) to Atg11 fragments, and examined the ability of the fusion proteins to complement the autophagy phenotype of atg11Δ. LZ fusion fully restored the ability of Atg11(522-552) to complement atg11Δ ( Figures 3F and 3G).…”
Section: Atg11(546-583) Mediates Homodimerizationmentioning
confidence: 99%
“…It was generally believed that FHA domains recognize unstructured sequences containing a phosphorylated amino acid –often a threonine. Recent studies, however, have shown that FHA domains can also use alternate surfaces for protein oligomerization and to mediate protein-protein interactions 15 16 17 18 19 . The Dbf4-dependent kinase (DDK) and Rad9 are two binding partners of Rad53 during the replication checkpoint response.…”
mentioning
confidence: 99%
“…Forkhead-associated (FHA) domain was first discovered in 1995 and later recognized for its unique structural feature , and specificity for binding phosphothreonine (pThr). This protein–phosphoprotein interaction motif is conserved in prokaryotes and eukaryotes . However, the flanking residues are much more diverse, , and phosphorylation-independent interactions have also been reported. , In contrast to its highly conserved β-sandwich architecture, which is composed of a five-stranded β-sheet and a six-stranded β-sheet, the loops connecting β-strands vary in length. Furthermore, FHA domains overall have a relatively low level of sequence homology.…”
mentioning
confidence: 99%